THE RELATIONSHIP BETWEEN LEARNING MOTIVATION WITH MATHEMATICAL PROBLEM SOLVING ABILITY IN CLASS XI STUDENTS: HUBUNGAN MOTIVASI BELAJAR DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA SISWA KELAS XI - Arisman Zebua; Heris Hendriana; Jozua Subandar; Asep Ikin Sugandi (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
The ability to solve problems is one of the cognitive abilities in mathematics that need to be mastered by students. In supporting mastery to solve problems, it is necessary to have the motivation to learn for students. This study aims to determine the relationship between learning motivation to students' mathematical problem-solving. The research method used is the correlation method with a quantitative approach. The population of this study was all students of class XI at Toma Nasional high school 2 and the sample selected was class XI science majors which collected 15 students. The instrument used in this research is a test to measure the ability to solve problems in the form of an explanation of 3 questions, while the non-test instrument to measure the level of learning motivation is in the form of a scale in the questionnaire. Data were analyzed using Pearson's product-moment correlation test. The results of this study indicate that at a significance level of 0.05 there is a relationship between learning motivation and students' problem-solving abilities. In addition, the linear regression equation Y = 12.964+0.422X is obtained, which means that for every additional 1 value of learning motivation, the mathematical problem-solving ability increases by 0.422.